Prevalence of Isolated Diastolic Hypertension and Associated Risk Factors among Different Ethnicity Groups in Xinjiang, China. - Fen Liu; Dilare Adi; Xiang Xie; Xiao-Mei Li; Zhen-Yan Fu; Chun-Fang Shan; Ying Huang; Bang-Dang Chen; Min-Tao Gai; Xiao-Ming Gao; Yi-Tong Ma; Yi-Ning Yang (PLoS ONE)
Objectives Little is known about isolated diastolic hypertension (IDH) among different ethnicity groups. We aimed to investigate the prevalence and risk factors for IDH among the major ethnicity population i.e. Han, Uygur and Kazakh in Xinjiang, northwestern part of China. Methods In total, 14,618 adult participants (7,799 males, 6,819 females) were recruited from the Cardiovascular Risk Survey conducted during 2007 and 2010. Blood pressure, body mass index and standard lipid profile and fasting glucose level from plasma were measured. Results The overall prevalence of IDH was 10.8% in the Han, 4.5% in the Uygur and 8.7% in the Kazakh populations. When stratified by gender, IDH prevalence was 9.8% in men and 6.8% in women (P<0.001). The prevalence of IDH also varied significantly with age and it was highest in those aged 35-44 yrs old (9.7%) and lowest in those over 75 yrs old (4.1%, P<0.001). Multivariate logistic regression analysis showed that overweight (OR = 1.179, 95%CI: 1.015-1.369) or obesity (OR = 1.202, 95%CI: 1.015-1.424), smoking (OR = 1.362, 95%CI: 1.156-1.604) and high total cholesterol (TC) hyperlipidemia (OR = 1.237, 95%CI: 1.074-1.423) were significantly associated with a higher prevalence of IDH. Identified risk factors for IDH differed among ethnicity groups with male gender, young age (35-44 yrs old), more coffee or tea consumption and high TC hyperlipidemia in the Han; smoking and often coffee or tea consumption in the Uygur and male gender and overweight or obesity in the Kazakh populations. Conclusions IDH prevalence in the Han population is higher than that in the Uygur and Kazak populations in Xinjiang, northwestern part of China. Male gender, middle age, overweight or obesity, smoking and high TC hyperlipidemia appear to be relevant risk factors of IDH in adults. Different ethnicity background had different sets of risk factors for IDH.